Novel Artificial Magnetic Conductor for 5G Application - Maizatun Muhamad; Maisarah Abu; Zahriladha Zakaria; Hasnizom Hassan (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
A design of novel bendable Artificial Magnetic Conductor (AMC) structures has been presented in this paper in two selected of frequencies at 5G application. These designs started with a square patch shape and continued with the combination of circular and Jerusalem shape which resonate at a frequency of 18 GHz and 28 GHz. Details of the theory and the structures of AMCs are explained. The reflection phase, bandwidth, angular stability and dispersion diagram were studied. The simulated results plotted that the novel AMC has good bandwidth and size is reduced by 53 percent and 55 percent for both frequencies. Other than that, it is also proved that the novel AMC has a stable reflection phase and no band gap performs at the specific frequency. The good performances of this novel AMC make it useful in order to improve antenna’s performance.